On a subclass of multivalent functions defined by generalized multiplier transformation - Alharayzeh Ma’moun I. Y. (Open Mathematics)
The objective of this study is to establish a novel category of multivalent analytic functions by utilizing generalized multiplier transformations. The subclass is further examined for coefficient estimations, growth and distortion theorems, extreme points, and the radius of starlikeness and convexity.